Pilot study of cerebrospinal fluid biomarkers reveals inflammatory changes in patients with paranoid schizophrenia - Franz Felix Konen; Philipp Sebastian Gehring; Hannah Benedictine Maier; Sebastian Schröder; Seda Nur Türker; Helge Frieling; Stefan Bleich; André Huss; Hayrettin Tumani; Daniel Lüdecke; Jürgen Gallinat; Berend Malchow; et al. (Scientific Reports)
Abstract Paranoid schizophrenia is a severe mental illness with both positive and negative symptoms. Currently, the role of peripheral and central inflammation is increasingly suspected as possible factor in the pathogenesis of schizophrenia. This retrospective, monocentric pilot study investigated 35 patients (15/35 female) diagnosed with paranoid schizophrenia after exclusion of possible underlying neuroinflammatory disorders to assess for inflammatory changes of the cerebrospinal fluid (CSF) and associated signs of neurodegeneration. Kappa free light chains (KFLC), a panel of 21 cyto- and chemokines, and neurofilament light chains (NFL) as surrogate parameters for neuro-inflammation and -degeneration were determined in patients with paranoid schizophrenia as well as age- and sex-matched inflammatory (n = 35) and non-inflammatory controls (n = 40). Patients with paranoid schizophrenia exhibited significantly higher intrathecal synthesized fractions of KFLC than non-inflammatory controls. KFLC-positive patients with paranoid schizophrenia had significantly higher NFL concentrations in CSF than KFLC-negative patients according to Reiber´s diagram. NFL concentrations in CSF of patients with paranoid schizophrenia were associated with illness duration, frequency of psychotic episodes, and amount of antipsychotic treatment attempts. This pilot study highlights inflammatory changes in the CSF among a specific subgroup of patients with paranoid schizophrenia, positively correlating with elevated NFL levels in CSF.